Antilipotoxicity Activity of Osmanthus fragrans and Chrysanthemum morifolium Flower Extracts in Hepatocytes and Renal Glomerular Mesangial Cells. (20th November 2017) - Tsai, Po-Jung; Chang, Mei-Ling; Hsin, Ching-Mei; Chuang, Chung-Chieh; Chuang, Lu-Te; Wu, Wen-Huey
Abstract : The excess influx of free fatty acids (FFAs) into nonadipose tissues, such as those of liver and kidney, induces lipotoxicity leading to hepatic steatosis and renal dysfunction. The aim of this study was to investigate the protective effects of methanolic flower extracts of Osmanthus fragrans (OF) and Chrysanthemum morifolium (CM) against FFA-induced lipotoxicity in hepatocytes (human HepG2 cells) and renal glomerular mesangial cells (mouse SV40-Mes13 cells). The results showed that OF and CM significantly suppressed FFA-induced intracellular triacylglycerol accumulation via partially inhibiting the gene expression of sterol regulatory element-binding protein-1c (SREBP-1c) and glycerol-3-phosphate acyltransferase (GPAT) in HepG2 cells. Both extracts inhibited reactive oxygen species (ROS) generation by FFA-stimulated HepG2 cells. OF and CM also suppressed the mRNA expression of interleukin- (IL-) 1 β, IL-6, IL-8, tumor necrosis factor- (TNF-) α, and transforming growth factor- (TGF-) β by HepG2 cells treated with conditioned medium derived from lipopolysaccharide-treated THP-1 monocytes. Furthermore, OF and CM effectively inhibited oleate-induced cellular lipid accumulation, TGF- β secretion, and overexpression of fibronectin in mesangial cells. In conclusion, OF and CM possess hepatoprotective activity by inhibiting hepatic fat load and inflammation and renal protection by preventing FFA-induced mesangial extracellular matrix formation.